The SAFER geodatabase for the Kathmandu Valley: Geotechnical and geological variability. Issue 3 (August 2020) - Gilder, Charlotte EL; Pokhrel, Rama Mohan; Vardanega, Paul J; De Luca, Flavia; De Risi, Raffaele; Werner, Maximilian J; Asimaki, Domniki; Maskey, Prem Nath; Sextos, Anastasios
The Kathmandu Valley is within a seismically active region with only few recorded strong-motion data. Geophysical information in the Valley is also sparse. In addition, the absence of an open database which compiles in situ geophysical tests, borehole records, and geotechnical laboratory data is affecting the advancement of knowledge in the region. This article presents SAFER/GEO-591 database, named after the Engineering and Physical Science Research Council (EPSRC)-funded project Seismic Safety and Resilience of Schools in Nepal (SAFER). SAFER/GEO-591 contains data from groundwater wells and boreholes originally commissioned for research and commercial purposes. This work describes (1) the quality assessment and harmonization process conducted on the dataset, (2) the variation of shear-wave velocity ( VS ) measurements and geotechnical parameters with depth and elevation in the Valley, (3) the current understanding of the Valley sediment/bedrock topography, and finally (4) new geological cross sections. A companion article presents an updated VS30 map across the Valley based on the contributions of this article. The database can be downloaded from the University of Bristol repository via DOI:https://doi.org/10.5523/bris.3gjcvx51lnpuv269xsa1yrb0rw